Synthesis of 5-Glucosyl-2,4-Isodithiobiurets and Their Antimicrobial Study - Korpe, G.V.; P. Deshmukh, S.; Musaddiq, M. (Asian Journal of Chemistry, 2010)
1-Aryl/(H)-5-tetra-O-benzoyl β-D-glucopyranosyl-2-S-benzyl 2,4-isodithio-biurets (3) have been prepared by the interaction of 1-aryl/H-2-S-benzyl-isothiocarbamides (1) with tetra-O-benzyol-β-D-glucopyranosyl isothiocyanate (2). Antibacterial and antifungal activities of these compounds were carried out on E. coli, S. aureus, P. vulgaris, Pseudomonas, Bacillus, Salmonella, A. niger and Fusarium. These compounds show sufficient activity towards these micro-organisms.